Identification, High-Density Mapping, and Characterization of New Major Powdery Mildew Resistance Loci From the Emmer Wheat Landrace GZ1 - Korchanová, Zuzana; Švec, Miroslav; Janáková, Eva; Lampar, Adam; Majka, Maciej; Holušová, Kateřina; Bonchev, Georgi; Juračka, Jakub; Cápal, Petr; Valárik, Miroslav (Frontiers in Plant Science, 2022)
Powdery mildew is one of the most devastating diseases of wheat which significantly decreases yield and quality. Identification of new sources of resistance and their implementation in breeding programs is the most effective way of disease control. Two major powdery mildew resistance loci conferring resistance to all races in seedling and adult plant stages were identified in the emmer wheat landrace GZ1. Their positions, effects, and transferability were verified using two linkage maps (1,510 codominant SNP markers) constructed from two mapping populations (276 lines in total) based on the resistant GZ1 line. The dominant resistance locus QPm.GZ1-7A was located in a 90 cM interval of a chromosome 7AL and explains up to 20% of the trait variation. The recessive locus QPm.GZ1-2A, which provides total resistance, explains up to 40% of the trait variation and was located in distal part of a chromosome 2AL. The locus was saturated with 14 PCR-based markers and delimited to 0.99 cM region which corresponds to 4.3 Mb of the cv. Zavitan reference genome comprising 55 predicted genes with no apparent candidate for the QPm.GZ1-2A resistance gene. No recessive resistance gene or allele was located at the locus before, suggesting presence of a new powdery mildew resistance gene in the GZ1. The mapping data and markers could be used for implementation of the locus in breeding. Moreover, they are an ideal base for cloning and study of host pathogen interaction pathways determined by the resistance genes.